Risks & Opportunities in the UK Energy Industry – 2013 and Beyond - Misra, Anandita (2013)
The UK energy market is grappling from lack of competition. Insufficient customer service, old technology and out-dated billing practices are some of the issues that are affecting the UK customers who are finding it difficult to keep control of their energy bills. While significant reforms are needed to create a competitive market, the industry is moving towards a customer-centric model. Today’s customer demand transparency related to their energy consumption and guidance from their suppliers on ways to save on their energy bills.